Youthful french in the graphic novel: An authentic multimodal vector for language hybridization - BOUMENDJEL , Lilia (Journal of Human Sciences, 2020)
In this study, we propose to examine the multimodal value of the graphic novel used in the teaching of foreign languages. To offer avenues likely to make the teaching / learning of young French more accessible, it is a question of highlighting the signs of language hybridization in this type of authentic multimodal supports, both in terms of visual, textual iconography or cultural. The deductions reveal the consequent potential of multidimensional exploitation which aims to bridge the gap between the classroom environment and the real life of the learners.